Consequences of Discontinuing a 4/6 Cyclin D-Dependent Kinase Inhibitor During Endocrine Treatment in Hormone-Sensitive Metastatic Breast Cancer Patients in the Context of the COVID-19 Outbreak - Martin, Sophie; Pflumio, Carole; Trensz, Philippe; Schaff-Wendling, Frederique; Weindling, Michal Kalish; Fischbach, Cathie; Pierard, Laure; Limacher, Jean-Marc; Nader, Rita; Velten, Michel; Petit, Thierry (Clinical breast cancer, 2023)
The impact of some hasty medical decision made during the first wave of the Coronavirus Disease 2019 (COVID-19) remains unknown. We have evaluated the consequences of one of these precautionary measures: the withdrawal of the cyclin D-dependent kinases 4/6 inhibitor (CDK4/6i) in patients whose metastatic disease was controlled by a combination of endocrine treatment and CDK 4/6i. This study was noninterventional, retrospective, multicentric, and included 60 patients with HR+ HER2- metastatic disease. Their disease was controlled with the combination of endocrine treatment and CDK 4/6i. The CDK 4/6i was stopped for two months during the first COVID-19 outbreak. A univariate analysis was performed to assess the risk factors associated with disease progression. During this therapeutic break, 22 (37 %) patients had a radiological and/or clinical disease progression. Among them, the CDK 4/6i was re-introduced to 16 patients (n = 16/22; 73 %). A new line of treatment (chemotherapy or targeted therapy) was initiated due to the rapid symptomatic tumor progression in four patients (n = 4/22; 18 %). Two patients (n = 2/22) died in visceral crisis before another anti-tumoral treatment was introduced. In univariate analysis, the presence of liver metastases increased the risk of metastatic disease progression during the withdrawal of the CDK 4/6 (OR = 6.6; 95 % CI 1.87-23.22; P= .0033). Progression was observed in 37% of patients during the two-month treatment interruption of the CDK 4/6i. A prolonged CDK 4/6i treatment interruption in patients with clinical benefit on endocrine treatment does not seem to be a reasonable option in light of these results. The impact of some oncology interventions taken hastily during the COVID-19 first wave remains unknown. This non-interventional, retrospective, multicentric study was conducted to assess the consequences of CDK 4/6i interruption in patients with metastatic breast cancer. Results showed disease progression in 37% of patients, and the risk of metastatic disease progression was significantly increased for patients with liver metastases.